Psychometric Properties of the Keratoconus Outcomes Research Questionnaire: A Save Sight Keratoconus Registry Study. Issue 3 (March 2020) - Kandel, Himal; Pesudovs, Konrad; Ferdi, Alex; Mills, Richard; Chen, Jern Yee; Watson, Adam; Poon, Alexander; Downie, Laura E.; Watson, Stephanie L.
Abstract : Purpose: The aim of this study was to evaluate the psychometric properties of the Keratoconus Outcomes Research Questionnaire (KORQ) in patients enrolled in the Save Sight Keratoconus Registry. Methods: A cross-sectional study was conducted utilizing prospectively collected web-based registry data. The psychometric properties of the KORQ were assessed using both classical test theory and Rasch analysis. Andrich group rating scale variant of the Rasch analysis was conducted using Winsteps software, Version 3.92.1. Results: The KORQ was completed by 189 patients with keratoconus (men, 67.7%; white, 69.8%; median age 29 years; better eye median values: visual acuity, 75 LogMAR letters; Kmax, 51.3 D; K2, 46.5 D; thinnest pachymetry, 485 μm). Cronbach's α for the "Activity Limitation" and "Symptoms" scales were 0.95 and 0.91, respectively, with both scales free from floor or ceiling effects. On Rasch analysis, the category thresholds were ordered and well-spaced for both scales. The Activity Limitation scale had excellent psychometric properties including person separation index (3.6), unidimensionality (variance explained, 65.4%), fit statistics (<1.3 MnSq), and measurement range (3.6 logits). Similarly, the Symptoms scale had satisfactory psychometric properties including person separation index (2.5), unidimensionality (variance explained, 54.3%), fit statistics (<1.30 MnSq except for 1 item), and measurement range (2.0 logits). Both scales were well targeted to the population and free of differential item functioning. Conclusions: The KORQ is a psychometrically robust patient-reported outcome measure for evaluating quality of life parameters in keratoconus. It enables routine collection and monitoring of meaningful patient-reported outcome data in clinical settings, including registries. Abstract : Supplemental Digital Content is Available in the Text.